2019
DOI: 10.1088/1538-3873/ab0075
|View full text |Cite
|
Sign up to set email alerts
|

The Apache Point Observatory Galactic Evolution Experiment (APOGEE) Spectrographs

Abstract: We describe the design and performance of the near-infrared (1.51-1.70 μm), fiber-fed, multi-object (300 fibers), high resolution (R = λ/Δλ ∼ 22,500) spectrograph built for the Apache Point Observatory Galactic Evolution Experiment (APOGEE). APOGEE is a survey of ∼10 5 red giant stars that systematically sampled all Milky Way populations (bulge, disk, and halo) to study the Galaxy's chemical and kinematical history. It was part of the Sloan Digital Sky Survey III (SDSS-III) from 2011 to 2014 using the 2.5 m Sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(125 citation statements)
references
References 73 publications
(119 reference statements)
0
116
0
3
Order By: Relevance
“…APOGEE is a high resolution, near infrared spectroscopic survey currently operating in both hemispheres, at Apache Point Observatory (APO; New Mexico, Gunn et al 2006) and Las Campanas Observatory (LCO; Chile, Bowen & Vaughan 1973). The APOGEE/DR16 dataset includes about 430,000 stars, collected between August 2011 and August 2018 using the two 300-fiber APOGEE spectrographs (Wilson et al 2019) and, for the first time, the APOGEE survey has near-complete coverage in Galactic longitude, due to the first release of data from LCO. The APOGEE data reduction pipeline (Nidever et al 2015;Holtzman et al 2015 provides stellar atmospheric parameters and radial velocity measurements, while elemental abundances are provided from the ASPCAP pipeline (García Pérez et al 2016;Mészáros et al 2012;Zamora et al 2015;Holtzman et al 2018, Jönsson et al, in prep).…”
Section: Datamentioning
confidence: 99%
“…APOGEE is a high resolution, near infrared spectroscopic survey currently operating in both hemispheres, at Apache Point Observatory (APO; New Mexico, Gunn et al 2006) and Las Campanas Observatory (LCO; Chile, Bowen & Vaughan 1973). The APOGEE/DR16 dataset includes about 430,000 stars, collected between August 2011 and August 2018 using the two 300-fiber APOGEE spectrographs (Wilson et al 2019) and, for the first time, the APOGEE survey has near-complete coverage in Galactic longitude, due to the first release of data from LCO. The APOGEE data reduction pipeline (Nidever et al 2015;Holtzman et al 2015 provides stellar atmospheric parameters and radial velocity measurements, while elemental abundances are provided from the ASPCAP pipeline (García Pérez et al 2016;Mészáros et al 2012;Zamora et al 2015;Holtzman et al 2018, Jönsson et al, in prep).…”
Section: Datamentioning
confidence: 99%
“…Jönsson et al 2020, in preparation) that will be made publicly available in 2019 December. This data release includes data taken from both the Northern and Southern Hemispheres using the APOGEE spectrographs (Wilson et al 2019) on the SDSS 2.5 m (Gunn et al 2006) and the 2.5 m du Pont (Bowen & Vaughan 1973) telescopes, respectively. The targeting procedure for APOGEE is presented in Zasowski et al (2013) and R. L. Beaton et al (2020, and details of the data reduction pipeline for APOGEE can be found in Nidever et al (2015).…”
Section: Datamentioning
confidence: 99%
“…APOGEE-2 is a near-infrared high-signal-to-noise ratio (S/N > 100 pixel −1 ), high-resolution (R ∼22,500) spectroscopic survey of over 450,000 Milky Way stars in the near-infrared H Band (1.5-1.7 µm). Observations were based on two twin NIR spectrographs (Wilson et al 2019) attached to the 2.5 m telescopes at Apache Point (Gunn et al 2006), and Las Campanas Observatories. Targets were selected in general from the 2MASS point-source catalogue, employing a dereddened (J − K s) ≥ 0.3 colour cut in up to three apparent H magnitude bins.…”
Section: Datamentioning
confidence: 99%